Transformation of the urban planning institutional structure in post-socialist transition: the example of the Sava waterfront in Belgrade - Maruna, Marija; Teofilovic, Vesna; Milovanovic Rodic, Danijela (Arhitektura i urbanizam, 2023)
The article researches the transformation of the urban planning institutional structure in the period of the post-socialist transition in Serbia. The goal is to provide an insight into the path of how urban planning has been modified due to structural changes in the socio-economic and political system in the period from 2000 to the present day. The focus of the research is the change in the role and position of institutions in decision-making processes on urban development, and especially the instruments used in those processes. Through a chronological review of the urban plans of New Belgrade blocks on the Sava Quay, several aspects of the planning process are observed: (a) changes in the planned uses of areas, (b) changes in the participation of institutions in the planning process and (c) changes in the instruments used in the planning process. The results of the research show that during the two decades of the post-socialist transition, urban planning was transformed in the direction of: (a) becoming a key instrument for the redistribution of spatial resources in favor of the interests of private capital; (b) the centralization of decision-making - vertically through the expanded influence of higher levels of government, and horizontally by the concentration of power within the group of decision-makers at the city level; and (c) the elaboration of decision-making mechanisms at the very end of the planning process and within a narrow circle of city government institutions, using the institute of amendments.